The Bet-Hedging Strategies for Seedling Emergence of Calligonum mongolicum to Adapt to the Extreme Desert Environments in Northwestern China - Fan, Baoli; Zhou, Yongfeng; Ma, Quanlin; Yu, Qiushi; Zhao, Changming; Sun, Kun (Frontiers in Plant Science, 2018)
Calligonum mongolicum is a dominant native perennial shrub on sand dunes in arid deserts of northwestern China, and is therefore widely used in sand dune stabilization in these regions. However, it remains largely unknown how seedling emergence of C. mongolicum has adapted to unpredictable sand movement and extreme drought. Here we examined effects of seed burial depth, light intensity, and seed age on seedling emergence, and considered seed germination and seedling emergence strategies for the shrub’s adaption to the desert environment. In our pot experiment, the optimum seeding depth for emergence of C. mongolicum was 2 cm, indicating that for germination and seedling emergence only moderate sand burial is required. Light intensity at the surface soil (0 cm) was important for seedling emergence, while there was no significant difference between 50 and 20% light flux density, at burial depths of 1 and 2 cm, indicating that C. mongolicum seeds had adapted to sand burial, while not exposure from sand erosion. We also found C. mongolicum seedlings emerged in spring and in late summer to early autumn. Meanwhile, seedling emergence percentage for 3-year-old seeds was similar to that of 1-year-old seeds, which meant that C. mongolicum seeds were well preserved under normal sand dune conditions, thus were capable of developing a persistent, but shallow soil seed-bank. These results indicated that germination and seedling emergence take a bet-hedging strategies to adapt to variable desert environments. Our study confirmed that C. mongolicum desert shrubs combine strategies in its adaption to arid and variable sand environments.